Audit in Belarus under new law and in new environment: first results, problems, prospects - S.L. Korotayev; A.V. Nemeroveс (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article analyzes the first results of application of the new law of the Republic of Belarus «On audit activity» since the 01.01.2014. The authors identify the problems inherent in auditing, propose specific measures to solve these problems, and to create the necessary conditions for the further development of audit.